Respuesta :

Answer: First option is correct.

Step-by-step explanation:

Since we have given that

[tex](\frac{2ab}{a^{-5}b^2})^{-3}[/tex]

We will use law of exponents :

[tex](\frac{2ab}{a^{-5}b^2})^{-3}\\\\=(\frac{a^{-5}b^2}{2ab})^3\text{ }\because (a^m)^{-1}=\frac{1}{a^m}\\\\=\frac{a^{-15}b^{6}}{8a^3b^3}\text{ }\because (a^m)^n=a^{mn}\\\\=\frac{b^{6-3}}{a^{3+15}}\\\\=\frac{b^3}{8a^{18}}[/tex]

So, the simplified form is

[tex]\frac{b^3}{8a^{18}}[/tex]

Hence, First option is correct.

Answer:

a. b^3/8a^18

Step-by-step explanation:

Just took the test